2020
DOI: 10.1021/acs.jpcb.0c03740
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Differentiators for Microscopic Structural Nonideality in Binary Ionic Liquid Mixtures

Abstract: Combining two ionic liquids to form a binary ionic liquid mixture is a simple yet effective strategy to not only expand the number of ionic liquids but also precisely control various physicochemical properties of resultant ionic liquid mixtures. From a fundamental thermodynamic point of view, it is not entirely clear whether such mixtures can be classified as ideal solutions. Given a large number of binary ionic liquid mixtures that emerge, the ability to predict the presence of nonideality in such mixtures a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…More recently, Kapoor and Shah found that the mixing behavior of binary IL mixtures could be inferred from the difference in the molar volumes of the pure ILs, in conjunction with the difference in the H-bond ability of the anions. These nonideal issues in IL mixtures were also recently investigated by Sappidi et al As mentioned in the Introduction, the H-bond basicity of IL pairs has been reported in some previous experimental investigations and using COSMO-RS approaches. , Here, we correlate the anion IPI with the H-bond basicity, as illustrated in Figure b and with the corresponding data listed in Table S6.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Kapoor and Shah found that the mixing behavior of binary IL mixtures could be inferred from the difference in the molar volumes of the pure ILs, in conjunction with the difference in the H-bond ability of the anions. These nonideal issues in IL mixtures were also recently investigated by Sappidi et al As mentioned in the Introduction, the H-bond basicity of IL pairs has been reported in some previous experimental investigations and using COSMO-RS approaches. , Here, we correlate the anion IPI with the H-bond basicity, as illustrated in Figure b and with the corresponding data listed in Table S6.…”
Section: Resultsmentioning
confidence: 99%
“…This chemical modification could incur variations in various properties of ILs, e.g., molar volume, viscosity, thermal stability and gas permeability. [34][35][36][37][38][39][40][41][42][43] A practical example is the decrease of the 1 H chemical shift of C2-H (hydrogen) of imidazolium cations upon the F-to-C2F5 mutation, suggesting a weakening effect on acidities. 44 Also, the low hydrolytic stability of [PF6]-involved ILs is overcome by incorporating the long-chain derivative [FAP].…”
Section: Introductionmentioning
confidence: 99%
“…Room temperature ionic liquids (RTILs) as a new type of green solvent are developing vigorously and becoming a research hotspot. RTILs are salts composed entirely of ions with a melting point below 373 K. [1][2][3] Compared with traditional organic solvents, they have many advantages such as non-volatility, high thermal stability, excellent solubility, and recyclability, [4][5][6] and have been widely used in extraction, 7,8 catalysis, 9,10 and electrochemistry. [11][12][13] The combination of ions in ILs can affect their characteristics, and the use of different anions can result in varying properties and applications of ILs.…”
Section: Introductionmentioning
confidence: 99%